A TEG-excited switched reluctance generator for self-powered sensing in next generation aircraft - Zaghari, Bahareh; Stuikys, Aleksas; Weddell, Alexander; Grabham, Neil; White, Neil; Harvey, Terry; Wang, Ling (AIAA, 2023)
New aircraft concepts are proposed to support emission reduction in aviation. To achieve the advantages of these concepts an electrical system with high power delivery and low system mass needs to be considered. The reduction of weight of all sub-components without compromising on reliability is being investigated. To achieve these self-powered systems can be introduced to monitor safety critical components. Locally embedded wireless self-powered systems can reduce the weight associated with health monitoring significantly compared to wired systems. In this paper a self-powered system that can be embedded in the engine is introduced. Switched reluctance generator integrated with a thermoelectric generator (TEG) is designed to provide power for bearing health monitoring. An efficient switched reluctance generator is designed for the limited amount of space in the aircraft engine. Two configurations for a six stator poles and fifteen rotor poles (6/15), three phase switched reluctance generator were compared and highest power output was obtained when the individual phase coils were connected in parallel. To achieve efficient energy conversion, the design process and selection of the excitation and generation angles played an important role.